Diseño de un sistema ecológico para la gestión de desechos sólidos en la comunidad Malinguapamba, cantón Sigchos, provincia de Cotopaxi - Sacatoro Toaquiza, María Enma (2016)
The aim of the research was to reduce the environmental disturbance caused by poor management of solid waste in the community of Malinguapamba, belonging to the canton Sigchos province of Cotopaxi during 2016; He started with a characterization of solid waste through fieldwork. the method of quartering which -consiste to group the waste generated by households, is divided into four one part reference is taken), it was able to classify the different wastes by their physical characteristics in Hazardous applied: (batteries, packaging fungicides and pesticides, drugs), 5%; non-hazardous (paper, cardboard, paper, cardboard, glass, packaging, etc.). With 50% and 45% organic and special materials (debris, tires, mattresses, furniture, shelves); Also harmful biodiversity was identified using the technique of direct observation and by using field records the presence of 3 species are rodents, insects and pets registered....